Dynamic general equilibrium modelling for forecasting and policy a practical guide and documentation of MONASH - Dixon, Peter B.; Rimmer, Maureen T. (Contributions to economic analysis, 2002)
The Contributions to Economic Analysis series consists of a number of previously unpublished studies. The term economic analysis is used because it covers the activities of the theoretical economist and the research worker.